Subtle Variations in Dietary-Fiber Fine Structure Differentially Influence the Composition and Metabolic Function of Gut Microbiota - Yunus E. Tuncil (American Society for Microbiology, 2020)
ABSTRACT The chemical structures of soluble fiber carbohydrates vary from source to source due to numerous possible linkage configurations among monomers. However, it has not been elucidated whether subtle structural variations might impact soluble fiber fermentation by colonic microbiota. In this study, we tested the hypothesis that subtle structural variations in a soluble polysaccharide govern the community structure and metabolic output of fermenting microbiota. We performed in vitro fecal fermentation studies using arabinoxylans (AXs) from different classes of wheat (hard red spring [AXHRS], hard red winter [AXHRW], and spring red winter [AXSRW]) with identical initial microbiota. Carbohydrate analyses revealed that AXSRW was characterized by a significantly shorter backbone and increased branching compared with those of the hard varieties. Amplicon sequencing demonstrated that fermentation of AXSRW resulted in a distinct community structure of significantly higher richness and evenness than those of hard-AX-fermenting cultures. AXSRW favored OTUs within Bacteroides, whereas AXHRW and AXHRS favored Prevotella. Accordingly, metabolic output varied between hard and soft varieties; higher propionate production was observed with AXSRW and higher butyrate and acetate with AXHRW and AXHRS. This study showed that subtle changes in the structure of a dietary fiber may strongly influence the composition and function of colonic microbiota, further suggesting that physiological functions of dietary fibers are highly structure dependent. Thus, studies focusing on interactions among dietary fiber, gut microbiota, and health outcomes should better characterize the structures of the carbohydrates employed. IMPORTANCE Diet, especially with respect to consumption of dietary fibers, is well recognized as one of the most important factors shaping the colonic microbiota composition. Accordingly, many studies have been conducted to explore dietary fiber types that could predictably manipulate the colonic microbiota for improved health. However, the majority of these studies underappreciate the vastness of fiber structures in terms of their microbial utilization and omit detailed carbohydrate structural analysis. In some cases, this causes conflicting results to arise between studies using (theoretically) the same fibers. In this investigation, by performing in vitro fecal fermentation studies using bran arabinoxylans obtained from different classes of wheat, we showed that even subtle changes in the structure of a dietary fiber result in divergent microbial communities and metabolic outputs. This underscores the need for much higher structural resolution in studies investigating interactions of dietary fibers with gut microbiota, both in vitro and in vivo.